Effect of Withaferin-A, Withanone, and Caffeic Acid Phenethyl Ester on DNA Methyltransferases: Potential in Epigenetic Cancer Therapy - Kumar, Vipul; Dhanjal, Jaspreet K.; Sari, Anissa Nofita; Khurana, Mallika; Kaul, Sunil C.; Wadhwa, Renu; Sundar, Durai (Current Topics in Medicinal Chemistry, 2024)
Background: DNA methyltransferases (DNMTs) have been reported to be potential drug targets in various cancers. The major hurdle in inhibiting DNMTs is the lack of knowledge about different DNMTs and their role in the hypermethylation of gene promoters in cancer cells. Lack of information on specificity, stability, and higher toxicity of previously reported DNMT inhibitors is the major reason for inadequate epigenetic cancer therapy. DNMT1 and DNMT3A are the two DNMTs that are majorly overexpressed in cancers. Objective: In this study, we have presented computational and experimental analyses of the potential of some natural compounds, withaferin A (Wi-A), withanone (Wi-N), and caffeic acid phenethyl ester (CAPE), as DNMT inhibitors, in comparison to sinefungin (SFG), a known dual inhibitor of DNMT1 and DNMT3A. Methods: We used classical simulation methods, such as molecular docking and molecular dynamics simulations, to investigate the binding potential and properties of the test compounds with DNMT1 and DNMT3A. Cell culture-based assays were used to investigate the inactivation of DNMTs and the resulting hypomethylation of the p16INK4A promoter, a key tumour suppressor that is inactivated by hypermethylation in cancer cells, resulting in upregulation of its expression. Results: Among the three test compounds (Wi-A, Wi-N, and CAPE), Wi-A showed the highest binding affinity to both DNMT1 and DNMT3A; CAPE showed the highest affinity to DNMT3A, and Wi-N showed a moderate affinity interaction with both. The binding energies of Wi-A and CAPE were further compared with SFG. Expression analysis of DNMTs showed no difference between control and treated cells. Cell viability and p16INK4A expression analysis showed a dose-dependent decrease in viability, an increase in p16INK4A, and a stronger effect of Wi-A compared to Wi-N and CAPE. Conclusion: The study demonstrated the differential binding ability of Wi-A, Wi-N, and CAPE to DNMT1 and DNMT3A, which was associated with their inactivation, leading to hypomethylation and desilencing of the p16INK4A tumour suppressor in cancer cells. The test compounds, particularly Wi-A, have the potential for cancer therapy.
Keywords: Therapy